O potrzebie wypowiadania się głosem = On the need to speak with a voice - Szewczyk-Kwitkowska, Jolanta (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The author shares experiences on artistic emissions. Presents exercise suggestions, emphasizes the importance of singing for health and also discusses the case of individual work with an adult.
Keywords: emisja głosu; ćwiczenia emisyjne; znaczenie kształcenia głosu; voice emission; emission exercises; the importance of voice training